2012
DOI: 10.4021/jocmr975w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-Month Sitagliptin Treatment on Glucose and Lipid Metabolism, Blood Pressure, Body Weight and Renal Function in Type 2 Diabetic Patients: A Chart-Based Analysis

Abstract: BackgroundSitagliptin is one of the dipeptidyl peptidase-4 (DPP-4) inhibitors which prevent the inactivation of incretins, increasing the endogenous active incretin levels. Incretins stimulate insulin secretion from pancreatic β-cells and inhibit glucagon secretion from pancreatic α-cells, which is favorable for the treatment of diabetes. Sitagliptin is released on December, 2009, in Japan. We retrospectively studied effects of 6-month-treatment with sitagliptin on glucose and lipid metabolism, blood pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
3
17
3
Order By: Relevance
“…We have previously reported that the 6-month sitagliptin treatment significantly reduced HbA1c, body weight in Japanese patients with type 2 diabetes [1]. We also found a negative correlation between changes in body weight and body mass index (BMI) at baseline, and also reported a negative correlation between changes in HbA1c and HbA1c levels at baseline [1].…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…We have previously reported that the 6-month sitagliptin treatment significantly reduced HbA1c, body weight in Japanese patients with type 2 diabetes [1]. We also found a negative correlation between changes in body weight and body mass index (BMI) at baseline, and also reported a negative correlation between changes in HbA1c and HbA1c levels at baseline [1].…”
mentioning
confidence: 53%
“…We also found a negative correlation between changes in body weight and body mass index (BMI) at baseline, and also reported a negative correlation between changes in HbA1c and HbA1c levels at baseline [1].…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Yanai et al [3] had found a significant and negative correlation between change in body Another study performed by Seck et al [4] result was for the PP cohort, Relative to baseline, sitagliptin was associated with significant weight loss (p<0.05) (-1.6 kg) compared with weight gain (+0.7 kg) with glipizide. Study conducted by Yang et al [5] in 2012 revealed a small decrease from baseline body weight in the placebo group compared with no change in the sitagliptin group (between-group difference 0.5kg; p<0.01).…”
Section: Methodsmentioning
confidence: 99%